Kekudusan Maria Sebagai Model Kekudusan Perempuan Kristiani Masa Kini: Tinjauan Biblis Dan Doktrinal Gereja - Siprianus Soleman Senda; Hironimus Pakaenoni; Theodorus A Silab; Oktovianus Kosat; Gabriel A.I. Benu (CARAKA: Jurnal Teologi Biblika dan Praktika, 2023)
One aspect that can be learned from the figure of a Mary in the Bible is her holiness. As a young woman or a virgin who was chosen to conceive and give birth to Jesus, the Son of God, Mary had a wealth of spirituality that today's Christian women can emulate. One of the riches of spirituality is its holiness. This study examines aspects of the holiness of Mary based on the Bible and the teachings of the Catholic Church. The method used is library research with a descriptive analysis approach. From an analysis of the holy texts and teachings of the Catholic Church, it is found that Mary has three dimensions of holiness, namely existential holiness, spiritual holiness and moral holiness. This holiness of Mary is a model for the holiness of Christian women today.